2014
DOI: 10.1093/pcp/pcu217
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Inhibits Root Growth by Reducing Auxin Accumulation via ARR1/12

Abstract: Plants exhibit reduced root growth when exposed to low temperature; however, how low temperature modulates root growth remains to be understood. Our study demonstrated that low temperature reduces both meristem size and cell number, repressing the division potential of meristematic cells by reducing auxin accumulation, possibly through the repressed expression of PIN1/3/7 and auxin biosynthesis-related genes, although the experiments with exogenous auxin application also suggest the involvement of other factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 60 publications
4
76
0
Order By: Relevance
“…We identified in our sweep list the birch ortholog of Arabidopsis transcription factor ARR1, a key regulator of Arabidopsis root meristem size 66 that mediates the balance between cell division and differentiation by integrating auxin and cytokinin responses. ARR1 is involved in cold-induced inhibition of root growth and reduced auxin accumulation 67 , and it also controls Arabidopsis drought susceptibility 68 . This may explain the link to the geographic and temperature variables detected here.…”
Section: Candidate Gene Adaptation Correlates With Environmentmentioning
confidence: 99%
“…We identified in our sweep list the birch ortholog of Arabidopsis transcription factor ARR1, a key regulator of Arabidopsis root meristem size 66 that mediates the balance between cell division and differentiation by integrating auxin and cytokinin responses. ARR1 is involved in cold-induced inhibition of root growth and reduced auxin accumulation 67 , and it also controls Arabidopsis drought susceptibility 68 . This may explain the link to the geographic and temperature variables detected here.…”
Section: Candidate Gene Adaptation Correlates With Environmentmentioning
confidence: 99%
“…CRF3 responds to auxin and is unresponsive to auxin in arf7, arf19, and arf7 arf19 mutant backgrounds ( Figure 1A; Supplemental Figure 8), suggesting that auxin may regulate CRF3 expression through ARF7 and ARF19. The previous studies showed that cold temperature inhibits root basipetal auxin transport and reduces auxin accumulation, limiting root growth in Arabidopsis (Shibasaki et al, 2009;Zhu et al, 2015), indicating that cold temperature inhibits auxin transport, biosynthesis, and response in the root. We speculate that the expression of CRF2 and CRF3 in response to cold may be an adaptation mechanism of plants under cold stress, enabling LR initiation and development to overcome the auxinmediated cold-induced inhibition of root growth, thus influencing changes in root system architecture in response to cold.…”
Section: Discussionmentioning
confidence: 96%
“…Cold stress inhibits root basipetal auxin transport by reducing the trafficking of the auxin efflux carrier PIN2 and inhibiting the lateral relocalization of PIN3 in Arabidopsis (Shibasaki et al, 2009). Cold reduces both root meristem size and cell number, repressing the division potential of meristematic cells by reducing auxin accumulation (Zhu et al, 2015). Thus, cold stress inhibits root growth partly by modulating auxin synthesis, transport, and response.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations